PENGARUH ABU SEKAM PADI DAN PUPUK SEPRINT TERHADAP PERTUMBUHAN DAN PRODUKSI TANAMAN SEMANGKA (Citrullus vulgaris Schard) - Alridiwirsah ,; Asritanarni Munar; Riko Ramdan A. Simamora (AGRIUM: Jurnal Ilmu Pertanian, 2011)
AbstractThis study aims to determine the effect of rice husk ash and fertilizer seprint as well as the interaction between rice husk ash and fertilizer on the growth and production seprint watermelon plants by using a design Plots Divided (Split Plot Design) with two factors studied namely rice husk ash as the main plots with namely two-stage treatment without rice husk ash (A0) and using rice husk ash (A1). Fertilizer seprint as subplot with three-stage treatment is a dose of 3 ml / L (S1), 6 ml / L (S2) and 9 ml / L (S3) while the measured parameter is the length of plant, age started flowering, age begin to harvest, diametre and the weight of fruits. Research suggests that the use of rice husk ash can significantly affect the parameters of fruit diameter, but not significantly affect the length of the plant parameters, age starts to flower and begin to harvest age. Fertilizer seprint not significantly affect the length of the plant parameters while the combination of rice husk ash and fertilizer seprint shows the interaction of the parameters of age began to flowering, age and weight began to harvest the fruitKey words: rice husk ash, fertilizer seprint, growth, production, watermelon